Examination of l‑Glutamic Acid Polymorphs by Solid-State Density Functional Theory and Terahertz Spectroscopy - Ruggiero, Michael T; Sibik, Juraj; Zeitler, J. Axel; Korter, Timothy M (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2016)
The ability of l-glutamic acid to crystallize in two different forms has long been the subject of study due to its commercial importance. While a solvent-mediated phase transformation between the α and β polymorphs is the prevailing theory, recent reports indicate a thermal solid–solid transformation between the two may be possible. However, determining accurate thermodynamic stabilities of these crystals has been challenging. Here new low-temperature single-crystal X-ray diffraction data coupled to solid-state density functional theory simulations have enabled a detailed description to be achieved for the energetic parameters governing the stabilization of the two l-glutamic acid solids. The temperature-dependent Gibbs free-energy curves show that α-glutamic acid is the preferred form at low temperatures (<222 K) and the β form is most stable at ambient temperatures. Terahertz time-domain spectroscopy was utilized to evaluate the quality of the intermolecular force modeling as well as to provide characteristic low-frequency spectral data that can be used for quantification of polymorph mixtures or crystal growth monitoring.